Penyeleksian Beasiswa Berprestasi pada Universitas XYZ Menggunakan Metode MOORA - Tundo Tundo; Panji Wijonarko (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2023)
XYZ University has a scholarship program intended for outstanding students. Determination of recipients of outstanding scholarships is still constrained by the unclear system for determining scholarship recipients. This can affect the fairness of receiving scholarships. Students who really deserve to get a scholarship do not receive the scholarship. The solution to overcome this problem, the researcher came up with an idea in the form of a Multi-Objective Optimization by Ratio Analysis (MOORA) Decision Support System method, with the aim of being able to solve the problem of selecting an objective scholarship acceptance process. The MOORA method was chosen because it can solve the problem with a fairly effective method. After conducting research, it was found that 5 (five) candidates were eligible to receive scholarships for outstanding students, namely Alt7, Alt10, Alt37, Alt49, and Alt35. Furthermore, from the results of this study, it was concluded that students who get achievement scholarships are students with the highest scores from the results of the MOORA method, there is no element of subjectivity.